Association of PH-Targeted Therapy and Survival in Precapillary PH with mPAP between 21 and 24 mmHg - Yogeswaran, Athiththan; Fünderich, Meike; Olschewski, Horst; Kovacs, Gabor; Kiely, David G; Lawrie, Allan; Hassoun, Paul M.; Balasubramanian, Aparna; Konswa, Ziad; Pepke-Zaba, Joanna; Cannon, John; Wilkins, Martin R.; et al. (My University, 2024)
Introduction: The definition of pulmonary hypertension (PH) was recently changed and led to a new subset of PH patients with mildly impaired pulmonary haemodynamics, characterised by a mean pulmonary artery pressure (mPAP) of 21–24 mmHg and with a pulmonary vascular resistance (PVR) >2 WU. We evaluated the association of PH-targeted therapy and outcome in mild precapillary PH using the PVRI GoDeep meta-registry. Methods: All patients with mild precapillary PH (mPAP 21–24 mmHg, pulmonary arterial wedge pressure ≤15 mmHg and PVR >2 WU) diagnosed with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) were enrolled. Patients were considered as “treated” if PH-targeted therapy was initiated within 6 months of diagnostic right heart catheterisation. Various statistical models, including in-depth sensitivity analyses, were used to examine the association between PH-targeted therapy and transplant-free survival. Results: 132 patients with group 1 or group 4 mild PH were identified, of whom 34 patients received PH-targeted therapy. There were no differences in baseline haemodynamics between untreated and treated groups, whereas treated patients suffered more frequently from renal comorbidities and required long-term oxygen treatment more often. Most prescribed were phosphodiesterase-5-inhibitors. PH-targeted therapy was associated with significantly higher survival rates. Cox-regression analyses revealed significantly reduced hazard ratios among treated patients adjusted for various confounders. Subgroup analyses in PAH (n=78) similarly indicated higher survival rates and reduced hazard ratios in treated patients. Conclusion: PH-targeted therapy may be associated with improved survival in PAH and CTEPH patients with mild PH. To mitigate potential bias of the results due to the retrospective study design, randomised controlled trials are warranted.
Keywords: ddc:610